2023
DOI: 10.1093/nar/gkad453
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosome RNA helicase KREH2 differentially controls non-canonical editing and putative repressive structure via a novel proposed ‘bifunctional’ gRNA in mRNA A6

Joshua Meehan,
Suzanne M McDermott,
Alasdair Ivens
et al.

Abstract: U-insertion/deletion (U-indel) RNA editing in trypanosome mitochondria is directed by guide RNAs (gRNAs). This editing may developmentally control respiration in bloodstream forms (BSF) and insect procyclic forms (PCF). Holo-editosomes include the accessory RNA Editing Substrate Binding Complex (RESC) and RNA Editing Helicase 2 Complex (REH2C), but the specific proteins controlling differential editing remain unknown. Also, RNA editing appears highly error prone because most U-indels do not match the canonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 71 publications
2
31
0
Order By: Relevance
“…Thus, KREH2 is the first known factor able to repress editing and regulate editing fidelity by governing global gRNA utilization. Our current studies on ND7 and prior work in other mRNAs (13,38) support a general regulatory model in which KREH2 has an unprecedented dual role able to stimulate or repress editing. In this duality, KREH2 controls the function of gRNAs, which specify both canonical or novel regulatory editing, in a substrate- and stage-dependent manner to modulate gene expression in any direction during development.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Thus, KREH2 is the first known factor able to repress editing and regulate editing fidelity by governing global gRNA utilization. Our current studies on ND7 and prior work in other mRNAs (13,38) support a general regulatory model in which KREH2 has an unprecedented dual role able to stimulate or repress editing. In this duality, KREH2 controls the function of gRNAs, which specify both canonical or novel regulatory editing, in a substrate- and stage-dependent manner to modulate gene expression in any direction during development.…”
Section: Introductionsupporting
confidence: 74%
“…R NA E diting Helicase KRE H2 -associated C omplex (REH2C) (4,5,15) contains three core proteins: the typifying DEAH-Box RNA helicase KREH2 and two directly bound helicase factors, the zinc finger protein KH2F1 and KH2F2. KREH2 controls editing fidelity (i.e., the ratio of non-canonical /canonical edits), including the first example of differential gRNA-directed non-canonical editing in PCF and BSF (38) ( Supplementary Table ST1 , glossary of terms). Sedimentation analyses suggested that REH2C may also have different variants (39).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA editing catalytic complex (RECC) and RNA editing substrate-binding complex (RESC) that comprise the bulk of the editing machinery are now much better understood than the genetic role of editing itself ( 17 , 27–29 ). RNA editing may also influence post-transcriptional regulation of gene expression in the absence of clearly identifiable gene-specific promoters on maxicircles and/or contribute to the variability and evolvability of kDNA ( 30 , 31 ). A final source of complexity is non-canonical editing events, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be established how the elaborate kDNA network can reliably partition, particularly since some essential minicircles are present in just a few copies amongst the ~10,000 duplicated minicircles prior to division (Gerasimov et al, 2021;S. J. Li et al, 2020;Meehan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%